Implementation of Reflective Learning Strategies to Improve Students' Comprehension Ability in Civics Lessons in Elementary Schools - Ainun Mardiah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
Reflective thinking is a student's ability to select knowledge that has been owned and stored in its memory to solve every problem it faces to achieve goals. This study aims to improve student learning outcomes by using a reflective learning model in Civics subjects. The subjects of this study were all 21 grade III students. While the object of this research is the results of student learning in Civics subjects with the theme "Rights and Obligations" with the application of a relective learning model. Data collection tools using observation and tests. Previously the learning process was carried out using the lecture method, question and answer, and assignments to students. As for the weaknesses in the learning process, namely the impact on learning understanding, there are misconceptions between teachers and students, a solution is needed to increase student understanding by applying a reflective learning model in Civics learning. It can be concluded that using a reflective learning model in the learning process can improve student learning outcomes when applied to Civics lessons in Class III Subsidized Swakarya Elementary School, Laut Dendang Village.